2008
DOI: 10.1111/j.1524-4725.2008.34287.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical 10% Zinc Sulfate Solution for Treatment of Melasma

Abstract: Topical 10% zinc sulfate solution is a new effective, safe, and noncostly formulation in the treatment of melasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 8 publications
0
24
0
2
Order By: Relevance
“…[1415] It has been suggested that zinc elements play role by anti-inflammatory, anti-oxidant, and healing effect. [11] In the present study, to our knowledge, we provide the first clinical evidence that compares quantitatively the effectiveness of topical 10% zinc sulfate and 4% hydroquinone cream in the treatment of melasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1415] It has been suggested that zinc elements play role by anti-inflammatory, anti-oxidant, and healing effect. [11] In the present study, to our knowledge, we provide the first clinical evidence that compares quantitatively the effectiveness of topical 10% zinc sulfate and 4% hydroquinone cream in the treatment of melasma.…”
Section: Discussionmentioning
confidence: 99%
“…[1112] Zinc sulfate was found to be effective in treatment of many dermatological disorders, such as cutaneous leishmaniasis, recurrent herpes simplex, common and genital warts and recently melasma. [1121415] In fact, there is only one study that has been conducted on the efficacy of topical zinc sulfate for the treatment of melasma. [1415] This study is the first, to our knowledge, to measure quantitatively the difference between the efficacy of conventional treatment with hydroquinone and the newly proposed agent, topical zinc sulfate solution in the treatment of melasma.…”
Section: Introductionmentioning
confidence: 99%
“…Topical zinc sulphate has also been tried in the management of melasma owing to its peeling and sunscreen properties. Sharquie et al [80] reported a significant reduction in MASI (melasma area and severity index) scores in 14 melasma patients after three months of therapy with 10% topical zinc sulphate without any significant adverse effects. However, this mode of treatment did not find much favor as results could not be reproduced in other studies and no statistically significant improvement was seen with topical zinc therapy [81, 82].…”
Section: Pigmentary Disordersmentioning
confidence: 99%
“…Of important note, vitamin B12 deficiency must be ruled out if a patient supplements with more than 1 mg per day because vitamin B12 deficiency and high serum folate are associated with an increased risk of cognitive impairment and anemia in adults (Selhub et al 2007). Also, patients with SOC are at a higher risk of melasma during pregnancy so photoprotection of the face is important during light therapy (Sharquie et al 2008). …”
Section: Special Considerationsmentioning
confidence: 99%